RAISING AWARENESS ON THE URGENT NEED TO IMPLEMENT FRAILTY INTO CLINICAL PRACTICE (J Frailty Aging, 2013)
Frailty has been linked to longer hospital stays and increased mortality in hospitalized patients. Frailty was found at the most common condition leading to death, followed by organ failure, cancer, other causes, advanced dementia, and sudden death. Yet despite evidence linking frailty to poor outcomes, frailty is not implemented clinically in most countries. Since many people are not identified as frail, they frequently are treated inappropriately in health care settings. Participants in the international conference on frailty emphasized the importance of raising awareness about frailty among geriatricians, general practitioners, and other primary care providers in order to implement frailty in clinical practice. The following recommendations were agreed upon: 1. Prioritize the identification of frail older persons in community settings, hospitals, and specialty clinics in order to ensure that people with frailty are treated appropriately and have access to interventional studies; 2. Build frailty clinics as a means of providing optimal management of frail elders; 3. Develop intervention programs incorporating physical and cognitive exercise, social support, and nutrition for people in the earliest stages of frailty in order to slow or reverse frailty; 4. Build stronger basic and clinical research programs in order to better understand the underlying causes of frailty, identify therapeutic targets, and develop new treatment strategies.